PRODUÇÃO DE GIRASSOL ANÃO SOBRE BANCADAS COM DIFERENTES MATERIAIS REFLETORES COLORIDOS EM AMBIENTE PROTEGIDO - ROCHA, Alana Silva; COSTA, Edilson; BARRETO, Andressa Fernanda Santos; ARAÚJO, Adrielly Patrícia Batista; NASCIMENTO, Ana Carolina Vidal do (ANAIS DO ENIC, 2025)
-